CLASSIFICATION OF NEOLOGISMS AND THEIR ACTUAL AREAS OF SEMANTIC RESEARCH AND FORMATION - Tursunova Farangiz Dildorbekovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Way of formation let us dwell on each criterion in more detail. Depending on the method, the appearance of neologisms is distinguished: lexical neologisms, which are created by productive word-formation models, and semantic ones, which arise as a result of assigning new meanings to already known words, and phraseological (neophrasemes). Formed as a result of assigning a new meaning to a phrase or expression most often, semantic derivation is manifested by metaphorization or metonymization, narrowing or expanding a previously known meaning.